PERLINDUNGAN HUKUM TERHADAP PASIEN SEBAGAI KONSUMEN JASA PELAYANAN KESEHATAN DALAM TRANSAKSI TERAPEUTIK - Achmad Muchsin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
In the therapeutic transaction, the relationship between patient and health service providers tends to bring the conflict. Many factors caused that conflict, e.g., lack of patient health understanding, inequality position between the patient and the provider before the law, and the imperfection of service quality handed over by the provider. Viewed from legal standing, therapeutic transaction has far consequences in reciprocal nature, between the patient and the doctor.